(untitled) (Proceedings of International Educators Conference, 2022)
Abdulla Qadiri-writer, poet, translator, dramatist, a great representative of the new Uzbek literature of the 20th century, the founder of Uzbek novels, an active participant in the important socio-cultural process of the 20th. Abdulla Qadiri is a great person who lived in a time when knowledge and enlightenment were as necessary for the people as air, when the country was ruled by ignorant people, and he did not stop sacrifing his life for his nation.